Advances in Distributed Computing and Machine Learning Proceedings of ICADCML 2020 - Tripathy, Asis Kumar; Sarkar, Mahasweta; Sahoo, Jyoti Prakash; Li, Kuan-Ching; Chinara, Suchismita (Lecture Notes in Networks and Systems, 2021)
XXII, 523 p. 241 illus., 165 illus. in color.